The Susceptibility of FPSO Vessel to Green Water in Extreme Wave Environment - Akandu, Ezebuchi; Incecik, Atilla; Barltrop, Nigel (Journal of Ocean, Mechanical and Aerospace -science and engineering-, 2014)
The Floating Production, Storage and Offloading (FPSO) vessels in harsh environment are often vulnerable to green water. Green water is the unbroken waves which overtop the bow, side or stern part of the deck of the floating offshore structure. It occurs when the relative motion between the vessel and the wave exceeds the freeboard. Green-water occurrence could lead to deck flooding and damage to deck-mounted equipment. It is therefore necessary to consider the vulnerability of the floating vessel to green water in the design stage. The objective of this research is to determine the optimal principal dimensions of FPSO vessel necessary to prevent or mitigate the effects of green water even in extreme wave environmental conditions. In order to achieve this, the effects of extreme environmental loads on the vessel have been evaluated in terms of the maximum responses in heave and pitch modes of motion. Furthermore, an interactive programme, the ProGreen has been designed to optimise the principal particulars based on the response and freeboard exceedance analyses for the required storage capacity of the FPSO. This design technique helps to prevent or reduce the green water occurrence, ensures good performance during operation and increases the level of safety and operability of the vessel even in extreme wave conditions.